The calculation technique for accelerating channel of the structure with the space-uniform RFQ focusing - Tishkin, S.S.; Bomko, V.A.; Zajtzev, B.V.; Kobets, A.F.; Sanin, V.M.; Shulika, N.G. (Вопросы атомной науки и техники, 2001)
Calculations were carried out for the initial part of the heavy ion accelerator with the large mass-to-charge ratio (a/q = 46). The process of calculation is divided in four stages. At the first stage the average aperture radius and the field strength are determined according to the initial data. At the second stage the optimization of the accelerating tract is performed. To the purpose, the structure is divided in 6 sections: a funnel (a cone), a bunch former, a pre-buncher, an adiabatic buncher, a booster, an accelerating section. At the third stage the obtained data are re-calculated in the values of the modulation depth and lengths of the accelerating periods with taking into account the real fields. At the fourth stage the beam parameters at the accelerator output are determined for the tract built with taking into account the space charge forces and the input beam parameters.